Leaving home - Keillor, Garrison (New York : Viking, 1987)
In this collection of stories about small-town life, Dale takes a step toward manhood and Darlene sets off for Minneapolis to begin a new life.
Introduction : a letter from Copenhagen -- A trip to Grand Rapids -- A ten-dollar bill -- Easter -- Corinne -- A glass of Wendy -- The speeding ticket -- Seeds -- Chicken -- How the crab apple grew -- Truckstop -- Dale -- High rise -- Collection -- Life is good -- Lyle's roof -- Pontoon boat -- State fair -- David and Agnes, a romance -- The killer -- Eloise -- The royal family -- Homecoming -- Brethren -- Thanksgiving -- Darlene makes a move -- Christmas dinner -- Exiles -- New Year's -- Where did it go wrong? -- Post office -- Out in the cold -- Hawaii -- Hansel -- Du, du Liegst mir im Herzen -- Aprille -- Goodbye to the lake.
"All of these stories were performed, in slightly different form, on 'A Prairie home companion, ' a production of Minnesota Public Radio"--P. [vi].
"This first edition ... is limited to a printing of fifteen hundred copies"--Prelims.
LC copy numbered: 23; signed in ink by Garrison Keillor; in slipcase.
Source: Copyright deposit, Oct. 28, 1987.
Also issued online.
Keywords: Lake Wobegon (Minn. : Imaginary place) -- Fiction; City and town life -- Fiction; Humorous stories, American; Minnesota -- Fiction